2009
DOI: 10.1080/01612840802641735
|View full text |Cite
|
Sign up to set email alerts
|

The Social Context of Sexual Health and Sexual Risk for Urban Adolescent Girls in the United States

Abstract: Sexually transmitted infections including HIV and teenage pregnancy have resulted in considerable morbidity and mortality among girls in the United States. There is a need to further strengthen prevention efforts against these persistent epidemics. In order to promote girls' sexual health and most effectively reduce sexual risk, it is important to understand the social factors that influence the development of a girl's sexuality. The purpose of this study was to begin to fill a void in the literature by explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 15 publications
6
73
0
Order By: Relevance
“…Although sex education is known to be difficult to deliver in school settings (25), previous studies have reported that school children in many countries identify textbooks or school as their primary source of health information (26)(27)(28)(29). The importance of information delivered in school settings has also been demonstrated by its long-term impact on healthy behaviors (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Although sex education is known to be difficult to deliver in school settings (25), previous studies have reported that school children in many countries identify textbooks or school as their primary source of health information (26)(27)(28)(29). The importance of information delivered in school settings has also been demonstrated by its long-term impact on healthy behaviors (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Studies commonly begin with statistics describing the high rates of STIs, HIV cases, or adolescent pregnancies in this population (e.g., Kennedy & Jenkins, 2011;Voisin & Bird, 2012)-rates that are substantially higher among Blacks than among Whites-and then go on to investigate variables that predict these sexual risk behaviors. However, it is argued that this approach to understanding the predictors of sexual behaviors provides only a limited perspective of sexual development (Teitelman, Bohinski, & Boente, 2009;Tolman & McClelland, 2011). Although it is vital that research continues to investigate the factors that contribute to alarming ethnic disparities in sexual outcomes, there Although the noted findings have been useful in beginning to document the role of parental communications in Black adolescents' sexual outcomes, the current literature base is limited in its scope.…”
mentioning
confidence: 94%
“…It should not be surprising that their questions reflect this dichotomy. What is concerning is that if adolescents hear from educators and parents only about the dangers of sex, they might cease to listen to them, and instead turn to the less reliable but more encouraging information they get from mass media or their peers (Bleakley, Hennessy, & Fishbein, 2011;Brown & Keller, 2000;Teitelman et al, 2009;Walsh-Childers, Gotthoffer, & Lepre, 2002).…”
Section: Downloaded By [University Of Guelph] At 19:38 06 February 2015mentioning
confidence: 95%
“…Add to this the highly sexualized environment in which they live, including media and pop culture that promote the pleasures of sexual behaviors and sexual relationships (Hust, Brown, & L'Engle, 2008;Brown & Keller, 2000;Teitelman, Bohinski & Boente, 2009), and it is easy to understand the desire for more information about how it is done, how it feels, and in some cases, permission to engage in those behaviors. At the same time, most young people are routinely warned about the dangers of sex, especially early sex or premarital sex, from conventional educational sources, and they receive these same messages at home (Fine & McClelland, 2006).…”
Section: Downloaded By [University Of Guelph] At 19:38 06 February 2015mentioning
confidence: 98%